2021
DOI: 10.1001/jamanetworkopen.2021.33132
|View full text |Cite
|
Sign up to set email alerts
|

The Association of ERBB2-Low Expression With the Efficacy of Cyclin-Dependent Kinase 4/6 Inhibitor in Hormone Receptor–Positive, ERBB2-Negative Metastatic Breast Cancer

Abstract: Among patients with HR+/ERBB2− MBC treated with CDK4/6 inhibitors, we observed that ERBB2-low expression was associated with an inferior PFS. This may serve as a potential marker candidate associated with CDK4/6 inhibitor efficacy. An intrinsic subtypes genomic analysis of the MONALEESA studies 3 found that, overall, the ERBB2-enriched (formerly HER2-enriched) subtype was associated with 2.3-fold increased risk of disease progression compared with the luminal A subtype. Our results provide phenotypical evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 5 publications
2
46
1
Order By: Relevance
“…HLBC-2E also showed an increase in CDK4 , PTEN , and RB1 signatures. Bao et al [ 30 ] have recently investigated the association between low levels of ERBB2 expression and clinical outcomes among patients with ER-positive/HER2-negative metastatic breast cancer patients treated with CDK4/6 inhibitors and described ERBB2-low expression as an independent predictor of inferior progression-free survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HLBC-2E also showed an increase in CDK4 , PTEN , and RB1 signatures. Bao et al [ 30 ] have recently investigated the association between low levels of ERBB2 expression and clinical outcomes among patients with ER-positive/HER2-negative metastatic breast cancer patients treated with CDK4/6 inhibitors and described ERBB2-low expression as an independent predictor of inferior progression-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the advanced setting, response rates to ADCs targeting HER2 are observed in about 30-50% of patients [ 4 6 ]. Furthermore, CDK4/6 inhibitors and PIK3CA inhibitors are standard of care for advanced luminal carcinomas, and as mentioned above, ERBB2 -low expression has been recently reported as an independent predictor of inferior progression-free survival [ 30 ]. Data on PIK3CA mutational status were not available for further stratification in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some scholars believe that bidirectional crosstalk between members of the human epidermal growth factor receptor family (HER) and the estrogen receptor (ER) is the basis of drug resistance; that is, high expression and amplification of HER2 drive the occurrence of endocrine resistance [ 150 ]. Kelvin et al investigated the relationship between HER2 expression levels and the efficacy of CDK4/6i combined with letrozole or fulvestrant therapy in ER+/HER2-negative BC patients [ 151 ]. In HER2-low BC, the PFS was significantly shorter than in HER2-0 (8.9 months vs. 18.8 months, p = 0.014) [ 151 ].…”
Section: Other Therapiesmentioning
confidence: 99%
“…Kelvin et al investigated the relationship between HER2 expression levels and the efficacy of CDK4/6i combined with letrozole or fulvestrant therapy in ER+/HER2-negative BC patients [ 151 ]. In HER2-low BC, the PFS was significantly shorter than in HER2-0 (8.9 months vs. 18.8 months, p = 0.014) [ 151 ]. HER2 upregulation is responsible for endocrine resistance, resulting in reduced PFS and pCR rates with overall endocrine therapy.…”
Section: Other Therapiesmentioning
confidence: 99%
“…A recent study analysed the association of HER2 low expression determined by immunohistochemistry score in HR positive and HER2 negative metastatic breast cancer subjects treated with CDK4/6 inhibitors. They found that the low expression of HER2 is associated with inferior progression-free survival [ 2 ] . However, not all patients achieve the expected survival outcome and become resistant to treatment regimens.…”
Section: Introductionmentioning
confidence: 99%